2016
DOI: 10.1074/jbc.m116.729384
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Inhibitors Targeting Tec Kinase Block Unconventional Secretion of Fibroblast Growth Factor 2

Abstract: Fibroblast growth factor 2 (FGF2) is a potent mitogen promoting both tumor cell survival and tumor-induced angiogenesis. It is secreted by an unconventional secretory mechanism that is based upon direct translocation across the plasma membrane. Key steps of this process are (i) phosphoinositide-dependent membrane recruitment, (ii) FGF2 oligomerization and membrane pore formation, and (iii) extracellular trapping mediated by membrane-proximal heparan sulfate proteoglycans. Efficient secretion of FGF2 is support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…Using an untagged version of FGF2 as a competitor for the interaction of His-tagged FGF2 and GST-tagged α1 constructs, the AlphaScreen ® assay also allowed for a quantitative comparison of the affinities between FGF2 and α1-CD1-3, α1-CD3 as well as α1-subCD3, respectively [ Fig. 2C; 15,41 ]. As reported previously, FGF2 binds to the complete cytoplasmic domain of α1 with an apparent KD of about 0.8 µM 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using an untagged version of FGF2 as a competitor for the interaction of His-tagged FGF2 and GST-tagged α1 constructs, the AlphaScreen ® assay also allowed for a quantitative comparison of the affinities between FGF2 and α1-CD1-3, α1-CD3 as well as α1-subCD3, respectively [ Fig. 2C; 15,41 ]. As reported previously, FGF2 binds to the complete cytoplasmic domain of α1 with an apparent KD of about 0.8 µM 15 .…”
Section: Resultsmentioning
confidence: 99%
“…11C and 12D). Following induction of protein expression with doxycycline, a well-established cell surface biotinylation assay was used to quantify the extracellular amounts of the FGF2-GFP fusion proteins indicated 20,23,41,43 . These experiments revealed that a K54/60E substitution alone caused a significant impairment of FGF2-GFP transport to the cell surface with only 60% efficiency compared to the wild-type form of FGF2-GFP ( Fig.…”
Section: Unconventional Secretion Of Fgf2-gfp Is Impaired Upon Substimentioning
confidence: 99%
“…Western blot was carried out as described before . The following antibodies were used: TEC, anti‐pY‐FGF2 , Actin (#3700), Nanog (#3580, Cell Signaling Technology, Danvers, MA), Oct4 (sc‐8629, Santa Cruz Biotechnology, Santa Cruz, CA, https://www.scbt.com/), FGF2 (F6162), SOX17 (AF1924, R&D Systems), FOX2A (H00003170‐M12, Novus Biologicals Europe, Abingdon, UK, https://www.novusbio.com/), α‐tubulin (11–250‐C100, Exbio, Prag, CZE, http://www.exbio.cz/), SOX2 (ab79351, Abcam, Cambridge, UK, http://www.abcam.com/), and PAX6 (DSHB Hybridoma Product PAX6, DSHB, Iowa City, IA, http://dshb.biology.uiowa.edu/). The protein bands were quantified using ImageJ (http://imagej.nih.gov/ij/).…”
Section: Methodsmentioning
confidence: 99%
“…Tec kinase itself is recruited to the inner leaflet via its N‐terminal pleckstrin homology domain in a phosphatidylinositol‐3,4,5‐triphosphate [PI(3,4,5)P 3 ]‐dependent manner (Shirai et al., ). The interaction of Tec kinase with FGF2 results in phosphorylation of FGF2 at tyrosine 81 (Figure ; highlighted in red) (Ebert et al., ; La Venuta et al., ). This modification is believed to have regulatory function tuning the efficiency of FGF2 secretion from cells (La Venuta et al., ).…”
Section: Unconventional Secretion Of Fgf2mentioning
confidence: 99%